Analisis Kelayakan Usaha Varian Minuman Herbal Hasil Praktek APHP Di SMKN 1 Plosoklaten Kediri - Atik Trisnaningsih; Arisyahidin Arisyahidin; Abu Talkah (Universitas Islam Kadiri, 2023)
The purpose of this study was to analyze the economic and financial viability of the herbal drink tamarind, soybean juice, and pineapple juice from the practice of APHP subjects at SMKN 1 Plosoklaten Kediri. The method in this study uses 3 analyzes, namely marketing aspects, HR and operational aspects, and financial aspects. The results of this study are based on the marketing aspect, SMKN 1 Plosoklaten has potential related to herbal drinks that have been produced by its students. SMKN 1 Plosoklaten needs to make the latest strategies related to the marketing of herbal beverage products so that the market reach is wider, based on HR and operational aspects, the students of SMKN 1 Plosoklaten have skills in making herbal drinks because they get assistance from professional teachers. The production of herbal drinks must be more continuous and scheduled so that sales can also be carried out continuously. Based on the financial aspect, the one with the most profitable business feasibility potential is the herbal drink with pineapple juice, while the one with the least profit is the soybean juice drink. SMKN 1 Plosoklaten needs to focus on the production of one of its herbal drinks so that it can carry out production and marketing continuously